Software Fault Tolerance Techniques for Dealing with Transient Faults in Satelite Software - Tahereh Broomandnezhad; Mohammad Abdollahi Azgomi; Shahrokh Jalilian (فصلنامه علوم و فناوری فضایی, 2013)
Satellite software is a kind of application that are exposed to soft-errors or transient faults because they work in an environment, which is full of radiations. This kind of fault has caused error in the execution of software. Satellite designers have used different methods, such as hardware shielding and component hardening, for removing the effects of this type of errors. These methods will increase the cost, weight and power consumption. Also, thesemethods decrease the performance. Recently, researches have shown that instead of spatial components,, COTS components can be used in LEO satellites. In addition, software implemented hardware fault tolerance (SIHFT) techniques can be added to these components for dealing with transient faults. In this paper, a branch of these techniques, which is called control flow based techniques, are investigated and the useful method among them is highlighted. The result of the implementation, testing and evaluation of the selected method (i.e. RSCFC) is also presented in this paper.